2012
DOI: 10.1002/jcp.24094
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of latent TGF‐β binding protein (LTBP) incorporation into matrix: Role of fibrillins and fibronectin

Abstract: Fibrillin microfibrils are extracellular matrix structures with essential functions in the development and the organization of tissues including blood vessels, bone, limbs and the eye. Fibrillin-1 and fibrillin-2 form the core of fibrillin microfibrils, to which multiple proteins associate to form a highly organized structure. Defining the components of this structure and their interactions is crucial to understand the pathobiology of microfibrillopathies associated with mutations in fibrillins and in microfib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
153
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(158 citation statements)
references
References 42 publications
4
153
0
1
Order By: Relevance
“…The complex of TGF-β and LAP (small latent complex) also requires anchoring to the ECM through its association with Ltbp1 and Ltbp3 . For Ltbp1, this incorporation is dependent on the assembly of fibronectin, and is independent of fibrillin expression, whereas incorporation of Ltbp3 is dependent on assembly of fibrillin 1 microfibrils (Zilberberg et al, 2012). To examine whether ΔItga5/av vSMCs could incorporate Ltbp1 into the matrix, we first analysed the ability of ΔItga5/av vSMCs to assemble endogenous fibronectin into fibrils.…”
Section: Loss Of α5 and αV Integrins Leads To Abnormal Tgf-β Signallingmentioning
confidence: 99%
See 1 more Smart Citation
“…The complex of TGF-β and LAP (small latent complex) also requires anchoring to the ECM through its association with Ltbp1 and Ltbp3 . For Ltbp1, this incorporation is dependent on the assembly of fibronectin, and is independent of fibrillin expression, whereas incorporation of Ltbp3 is dependent on assembly of fibrillin 1 microfibrils (Zilberberg et al, 2012). To examine whether ΔItga5/av vSMCs could incorporate Ltbp1 into the matrix, we first analysed the ability of ΔItga5/av vSMCs to assemble endogenous fibronectin into fibrils.…”
Section: Loss Of α5 and αV Integrins Leads To Abnormal Tgf-β Signallingmentioning
confidence: 99%
“…Interestingly, a recent study has shown that assembly of the glycoprotein fibronectin, rather than fibrillin 1, is essential for incorporation of Ltbp1 into the ECM by vSMCs (Zilberberg et al, 2012). Fibronectin is one of the first ECM proteins to be expressed around the vasculature and is essential for cardiovascular development (Astrof and Hynes, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…TGF-β is secreted to the ECM in an inert/latent form complexed with much larger proteins that encapsulate TGF-β, the latency associated peptide (LAP) and latent TGF-β binding protein-1 (LTBP-1), which interface TGF-β between the fibronectin molecule in the ECM and the integrin receptors in the PSCs surface [37,38]. A spatiotemporal organisation of cellular and ECM mechanical factors including PSC contractility release TGF-β in its active form [39,40] autocrine and paracrine loop that sustains PSC activation and a tumour-favouring microenvironment.…”
Section: Reprogramming Cell Mechanics Induces Quiescence In Pscs Supmentioning
confidence: 99%
“…According to these data, an additive minor allele model fitted best in describing the association between rs2118181 and aneurysm (odd ratio latent complex from proteolytic activation or whether FBN1 functions more directly in controlling assembly or stability of latent TGF-β1 complexes (14). Second, the balance between the need for TGF-β1 in normal development and suppression of its activity in the treatment of disease should be considered (15).…”
Section: Determination Of Genotypesmentioning
confidence: 99%